2019
DOI: 10.7150/thno.34412
|View full text |Cite
|
Sign up to set email alerts
|

Protein Delivery into the Cell Cytosol using Non-Viral Nanocarriers

Abstract: Protein delivery into cells is a potentially transformative tool for treating “undruggable” targets in diseases associated with protein deficiencies or mutations. The vast majority of these targets are accessed via the cytosol, a challenging prospect for proteins with therapeutic and diagnostic relevance. In this review we will present promising non-viral approaches for intracellular and ultimately cytosolic delivery of proteins using nanocarriers. We will also discuss the mechanistic properties that govern th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 96 publications
0
83
0
Order By: Relevance
“…The direct delivery of protein complexes is advantageous in situations where other strategies such as viral vectors or plasmid DNA can lead to cytotoxicity, off-target effects, or low control over protein expression. [49,50] Gene-editing studies employing CRISPR/Cas9 systems, [51,52] induction of pluripotency for tissue engineering, [53] and stimulation of immune cells for therapeutic purposes are avenues where direct protein delivery using the NFP-E might prove beneficial. We have also shown that the NFP-E approach can attain relatively high transfection efficiency in normal cell culture medium without requiring a media change.…”
Section: Discussionmentioning
confidence: 99%
“…The direct delivery of protein complexes is advantageous in situations where other strategies such as viral vectors or plasmid DNA can lead to cytotoxicity, off-target effects, or low control over protein expression. [49,50] Gene-editing studies employing CRISPR/Cas9 systems, [51,52] induction of pluripotency for tissue engineering, [53] and stimulation of immune cells for therapeutic purposes are avenues where direct protein delivery using the NFP-E might prove beneficial. We have also shown that the NFP-E approach can attain relatively high transfection efficiency in normal cell culture medium without requiring a media change.…”
Section: Discussionmentioning
confidence: 99%
“…With a near atomic resolution (57), EM is an irreplaceable tool in studying the physio-chemical properties of NP and quantifying their voyage through the endo-lysosomal pathway (30,37,(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74). EM can even detect a low number (few hundreds) of single nanoparticles escaping endosomal structures, and since it is a label-free method, it will localise and quantify NP generally untraceable by standard light microscopy methods.…”
Section: Electron Microscopy and Cryo-electron Microscopymentioning
confidence: 99%
“…Various papers study the endosomal escape of NP using several independent microscopic techniques (30,58,68,140,141). However, a correlative approach is more desirable, as it Up to date, the only CLEM approach used to quantitatively study endo-lysosomal tracking of NP has been developed by Han et al (74) (Fig.…”
Section: Correlative Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Several other approaches are also being pursued to deliver recombinant proteins into mammalian cells, including physical methods, 17 fusion with bacterial toxins, 18 surface modification, [19][20][21] complexation with cationic peptides and polymers, [22][23][24][25] and encapsulation into nanoparticles and liposomes. 26,27 Each of these approaches has its advantages but also faces unique challenges. Protein delivery by physical methods is generally incompatible with clinical applications, except for topical administration.…”
Section: Introductionmentioning
confidence: 99%